Community participation in Blangsinga tourism village development - Martini, Ni Ketut Ayu (International research journal of management, IT and social sciences, 2020)
This study aims to determine the form of community participation and strategies to increase community participation in Blangsinga Tourism Village. The theory used in this study is Community Based Tourism (CBT). The type of data used in this study is qualitative data which is data in the form of information either in the form of direct interviews or documents related to research. Data sources used are divided into two, namely primary data and secondary data. Based on the results of the research conducted, it can be concluded that the development of Blangsinga Tourism Village is inseparable from the participation of the community. The form of Blangsinga community participation in the planning and implementation stages. Efforts to increase community participation are carried out by the village government and third parties by making policies that certainly have a positive impact on the community and the development of Blangsinga Tourism Village.